2019
DOI: 10.9734/ejmp/2019/v30i230170
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Knowledge and Practice of Herbal Remedy Use among the Population Visiting Pharmacies and Health Care Providers in Alexandria, Egypt: A Cross-Sectional Study

Abstract: Aims: To show the levels of awareness, attitude, practices and socioeconomic factors related to consuming herbal products among Alexandrian citizen visiting pharmacies. The findings of this study are meant also to show the practices and beliefs of healthcare providers regarding using herbal remedies in treatment, including advising patients, reporting adverse effects and possessing knowledge about specific herb-drug interactions. Study Design:  people visiting pharmacies as well as pharmacists in their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, the overall comparison found that the GP had better knowledge than HCWs about herbal medicine regarding their use during the COVID-19 as immune-boosting but not protective agents. In line with this nding, several studies reported that HCWs need further education and training on herbal medicine to improve their knowledge (Hilal and Hilal, 2017;Kemper et al, 2003;Sherif et al, 2019). The explanation of the GP's good knowledge in the current study could be that the GP continued looking for natural immune-boosting agents to protect themselves against the coronavirus infection during the pandemic, and the in uence of cultural beliefs on Islamic and traditional medicine in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the overall comparison found that the GP had better knowledge than HCWs about herbal medicine regarding their use during the COVID-19 as immune-boosting but not protective agents. In line with this nding, several studies reported that HCWs need further education and training on herbal medicine to improve their knowledge (Hilal and Hilal, 2017;Kemper et al, 2003;Sherif et al, 2019). The explanation of the GP's good knowledge in the current study could be that the GP continued looking for natural immune-boosting agents to protect themselves against the coronavirus infection during the pandemic, and the in uence of cultural beliefs on Islamic and traditional medicine in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, several studies not related to the pandemic found that HCWs expressed the need for further education regarding herbal use (Hilal and Hilal, 2017;Sherif et al, 2019). However, to the best of our knowledge, no study has compared the knowledge and attitude of GP and HCWs towards herbal therapy.…”
Section: Introductionmentioning
confidence: 97%
“…A questionnaire was developed in accordance with previously published studies 5 , 22 , 27 , 39 to assess the level of knowledge about the use of herbs and natural product as protective measures during the COVID-19 pandemic of the GP and HCWs. The questionnaire was reviewed by four individuals who were experts in medical immunology, family medicine, preventive medicine, and clinical nutrition to evaluate its appropriateness and adequacy.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies not related to the pandemic found HCWs expressed a need for further education regarding the use of herbal medicine. 17 , 27 However, to the best of our knowledge, no study has compared the knowledge about and attitude toward herbal medicine between the GP and HCWs. Therefore, the current study aimed to compare the knowledge about and attitude toward the use of herbs and natural products as a protective measure during the COVID-19 pandemic between HCWs and the GP in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Although, herbal medicine side effects were reported by 25% of herbal medicine user. Most of respondents did not inform practitioner about use of herbal medicine and HCP did not ask, as they lack knowledge about medicinal plants (Fathy et al, 2019). On the account of men being less inclined to search for information HCP should be more proactive in consulting them about safe use of medicine.…”
Section: Figure 2 Initiators For the Beginning Of Using Herbal Preparationsmentioning
confidence: 99%